Mid-term results of lateral unicondylar mobile bearing knee arthroplasty: a multicentre study of 363 cases - Walker, Tilman; Zahn, Niklas; Bruckner, Thomas; Streit, Marcus R.; Gotterbarm, Tobias (The bone & joint journal, 2018)
AIMS: The aim of this independent multicentre study was to assess the mid-term results of mobile bearing unicondylar knee arthroplasty (UKA) for isolated lateral osteoarthritis of the knee joint. - PATIENTS AND METHODS: We retrospectively evaluated 363 consecutive, lateral UKAs (346 patients) performed using the Oxford domed lateral prosthesis undertaken in three high-volume knee arthroplasty centres between 2006 and 2014. Mean age of the patients at surgery was 65 years (36 to 88) with a mean final follow-up of 37 months (12 to 93) RESULTS: A total of 36 (10.5%) patients underwent revision surgery, giving a survival rate of 90.1% at three years (95% confidence intervals (CI) 86.1 to 93.1; number at risk: 155) and 85.0% at five years (95% CI 77.9 to 89.9; number at risk: 43). Dislocation of the mobile bearing occurred in 18 patients (5.6%) at three years (95% CI 1.0 to 16.4; number at risk: 154) and in 20 patients (8.5%) at five years (95% CI 1.0 to 27.0; number at risk: 42). There were no significant differences in the dislocation rate between the participating centres or the surgeons. We were not able to identify an effect of each surgeon's learning curve on the dislocation rate of the mobile bearing. The clinical outcome in patients without revision surgery at final follow-up was good to excellent, with a mean Oxford knee score of 40.3 (95% CI 39.4 to 41.2), a mean Tegner activity score of 3.2 (95% CI 3.1 to 3.3) and a mean University of California, Los Angeles score of 5.7 (95% CI 5.5 to 5.9). - CONCLUSION: Our data, which consists of a high number of patients treated with mobile bearing UKA in the lateral compartment, indicates a high revision rate of 15% at five years with dislocation of the mobile bearing being the main reason for implant failure. Despite the good functional and clinical results and the high patient satisfaction in our study group, we therefore discontinued using mobile-bearing lateral UKA in favour of a fixed-bearing component. Cite this article: Bone Joint J 2018;100-B:42-9.
Gesehen am 25.04.2019